Exercise Obsession and Compulsion in Adults With Longstanding Eating Disorders: Validation of the Norwegian Version of the Compulsive Exercise Test - Vrabel, Karianne; Bratland-Sanda, Solfrid (Frontiers in Psychology, 2019)
Objectives: The objectives of this study were to 1) validate the Norwegian version of the Compulsive Exercise Test (CET) in adults with longstanding eating disorders, and 2) explore predictors of high CET-score. Methods: Adult inpatients with longstanding DSM-IV Anorexia Nervosa, Bulimia Nervosa or Other Feeding or Eating Disorders (n=166) completed the CET instrument, Eating Disorders Examination – Questionnaire (EDE-Q), Beck Depression Inventory-II (BDI-II) and Symptom checklist-90 (SCL-90). A total CET score of ≥15 was defined as high CET-score. ANOVA, Confirmatory factor analysis, Pearson’s correlation, and logistic regression was used to analyze the data. Results: The confirmatory factor analysis showed adequate fit. Convergent validity of the CET demonstrated correlation between EDE-Q global and subscale scores and CET total score. The same pattern was found for correlation between CET subscales and EDE-Q subscales. EDE-Q global score and frequency of exercise episodes predicted high CET-score, yet 21% of the patients with high CET score had <one episode of exercise per week. Conclusion: The Norwegian version of CET is valid and useful for assessing compulsive exercise in a sample with longstanding ED. The understanding of compulsive exercise must to a greater extent differ between obsessions and compulsions, as a significant number of patients with high CET score showed no or little exercise behavior.